Pengaruh Substitusi Bungkil Kacang Kedelai dengan Tepung Daun Singkong dalam Ransum terhadap Penampilan Produksi Broiler - Noviadi, R. (Jurnal Penelitian Pertanian Terapan, 2010)
An experiment was done at Poultry Cage Trial and Laboratory of Animal Husbandry, Departement of Animal Husbandry, The State Politechnic of Lampung. The experiment began in 10th June until 10th August 2009. The experiment were conducted to know the Effect of substitution soy bean meal with cassava leaf meal in ration on broiler performance. The treatment and method by used was consist four treatments. These used 96 birds as replication. The birds were placed randomizely divided into 4 treatments and 6 replications, that treatment were R0= 0%, R1= 3,75%; R2 = 7,50%, and R3 =11,2,5% cassava leaf meal on ration. Parameter measured were : feed consumtion, body weight gain and feed conversion ratio. The experiment was done based on Completely Randomized Design (CRD) and test significance the continued Duncan Multiple Range. The result of this experiment showed that the substitution of soy bean meal with cassava leaf meal can be used to 7,50% in broiler ration. Key words : cassava leaf meal, soy bean meal, broiler